Experimental and theoretical investigation of mesoporous MnO2 nanosheets with oxygen vacancies for high-efficiency catalytic DeNOx - Liu, Jia (2020)
A solvent-free synthetic method was employed for the construction of mesoporous α-MnO2 nanosheets. Benefiting from a solid interface reaction, the obtained MnO2 nanosheets with large oxygen vacancies exhibit a high surface area of up to 339 m2/g and a mesopore size of 4 nm. The MnO2 nanosheets as a catalyst were applied in NH3-assisted selective catalytic reduction (NH3-SCR) of DeNOx at a relatively low temperature range. The conversion efficiency could reach 100% under a gas hourly space velocity (GHSV) of 700000 h−1 at 100 °C. To gain insight into the mechanism about NH3-SCR of nitric oxide on the MnO2 nanosheets, temperature-programmed desorption of NH3, a density functional theory study, and in situ diffuse reflectance infrared Fourier transform spectra were carried out, revealing the cooperative effect of catalytic sites on the reduction of nitric oxide. This work provides a strategy for the facile preparation of porous catalysts in low-temperature DeNOx.